Effects of dietary vitamin E and selenium on arginase activity in the liver, kidneys, and heart of rats treated with high doses of glucocorticoid - Erisir, M; Beytut, E; Ozan, S; Aksakal, M (John Wiley & Sons Ltd, 2003)
The effects of dietary intake of vitamin E and selenium on arginase activity in the liver, kidneys, and heart of rats treated with high doses of prednisolone were investigated. Rats were divided into five groups. Groups 3, 4, and 5 received a daily supplement in their drinking water of vitamin E, Se, and a combination of vitamin E and Se, respectively, for 30 days. For 3 days subsequently, the control group (group 1) was given a placebo, and the remaining four groups were injected intramuscularly with prednisolone. The tissue samples were collected from each group at 4, 8, 12, 24, and 48 h after the last administration of prednisolone. In the group treated with prednisolone alone, arginase activity in the liver was found to have increased at all the time periods, whereas it had decreased significantly in the heart at 48 It. Arginase activity in the kidneys was not affected by prednisolone. Compared to the control and prednisolone groups, arginase activity in the kidneys and heart of the vitamin E- and Se-supplemented groups was found to be significantly increased at all time periods, however, no difference was seen in the combination group. Arginase activity in the liver of the vitamin E-supplemented group was found to have decreased at all time periods, however, in the Se group compared to the prednisolone group it had reduced at 24 and 48 h only. In the combination group compared to the prednisolone group, liver arginase activity increased constantly up to 12 h returning to normal values at 48 h. Vitamin E and Se in combination may prevent the changes in arginase activity in various tissues caused by prednisolone. Copyright (C) 2003 John Wiley Sons, Ltd.
Keywords: arginase; glucocorticoid; vitamin E; selenium; liver; kidney; heart